RF energy harvesting systems for autonomous wireless sensor - Delos Reyes, Mark Gerard Trinos (College of Engineering, University of the Philippines Diliman, 2013)
Recent studies show that the power consumtion of wireless sensor networks (WSNs) has already been reduced significantly down to a level where energy harvesting can be a feasible alternative energy source. There are severeal possible energy sources such as vibration, solar, thermal, or RF, which can act as a replacement for conventional sources of power. Among these, RF energy harvesting sees greatest potential as it exists in almost every environmental conditions unlike other energy sources. In this study, research is geared towards the optimization of a complete energy harvesting interface. Most of existing researches focused only with the improvement of individual blocks which is difficult to apply in real applications. A proposed energy harvesting system is implemented using a power-matching step-up transformer to drive the RF-DC converter block for efficient energy harvesting. For the RF-DC converter topologies, only passive RF-DC converter topologies are studied to avoid complexity and to save power from additional elements such as clocks and voltage references. Three topologies--modified Dickson voltage multiplier, Mandal-Sarpeshkar voltage multiplier, and Villard voltage multiplier--are chosen to be implemented and compared in terms of their conversion efficiency, power, and, area. A test chip containing the proposed energy harvesting interface is fabricated in a standard 90nm CMOS process. Measurement results showed that the proposed architecture is able to convert RF energy and produce 1V DC voltage at the outputs. The transformers attained a minimum insertion loss of 20dB. The modified Dickson topology performed the best with a power efficiency of 25%.